Growth and Survival of Chilgoza Seedlings as Influenced by Different Types and Size of Sowing Media - Noori, Abdul Matin; Salari, Hedayatullah; Zazai, Khanzad Gul; Larawai, Mohammad Ismael (Journal for Research in Applied Sciences and Biotechnology, 2024)
Chilgoza pine (Pinus gerardiana Wall.) is an important but endangered tree species in Afghanistan. Due to poor natural regeneration, seed-related dormancy and anthropogenic factors, the IUCN put this species on the red list. Therefore, this study was undertaken to investigate the effect of growing medium and polybag sizes on seedling growth and survivability. In this study, four growing media of soil (So), compost (Co), forest soil (Fs) and sand (Sa), viz., M1 (So + Co + Fs); M2 (Fs + Co + Sa); M3 (So + Fs + Sa); and M4 (Sa + Co + Fs) and three polybag sizes including P1 (16 cm×16 cm), P2 (18 cm×18 cm), and P3 (21 cm×26 cm) were used and arranged in the frame of 4×3 factorial design to assess their effects on seedling growth and survivability. The results revealed that among different growing media treatments, higher seedling growth parameters and survival rate percentage were observed on treatment M4 (Sand + Compost + Forest Soil). Seedling growth parameters and survivability were significantly affected by polybag size, and the highest seedling growth parameters and survival rate were obtained for Large Polybag size (P3).